Educational Analysis of Language Style Errors on Facebook Social Media: Captions and Comments on Islamic Content - Satriah, Satriah; Yasin, Muhammad; Widyanti, Eka; Jannah, Siti Sri Fattul (Lembaga Pendidikan Hikmatun Najah Blora, 2024)
One way to write comments and make posts in captions is to use languages commonly used on Facebook social media platforms in everyday life, such as Indonesian, local dialects, or English. The aim of this study is to describe the misuse of the Indonesian language on Facebook in Islamic content and to highlight the misunderstandings in the use of the Indonesian language on Facebook in Muslim content. This study employs a qualitative method, analyzing errors in caption language style and comments on Facebook's Islamic content, used as a communication medium to exchange thoughts among users. The results reveal errors in the use of Indonesian on Facebook in Islamic content, including spelling errors, improper dictionary use, and grammatical errors. Additionally, misunderstandings in the use of Indonesian on Facebook in Muslim content arise from variations in communication styles among users. To improve the quality of Indonesian language use in Islamic content on Facebook, it is necessary to undertake education that covers both language aspects and a deep understanding of Islamic values.